Rapid diagnosis of Entamoeba infection by using Entamoeba and Entamoeba histolytica stool antigen detection kits. - Haque, R (1995)
Humans are infected by two morphologically identical species of Entamoeba: Entamoeba histolytica causes amebic colitis and liver abscess, and Entamoeba dispar is noninvasive. Several weeks of culture and isoenzyme (zymodeme) analysis are required to differentiate E. histolytica from E. dispar. Here we report a field trial of commercial antigen detection kits designed to rapidly detect and differentiate E. histolytica from E. dispar in stool specimens. Stool specimens from 202 patients with diarrhea were examined for E. histolytica and E. dispar by microscopy, culture, and antigen detection. Compared with culture, microscopic identification of the E. histolytica-E. dispar complex was 60% sensitive and 79% specific, while the screening antigen detection test for the E. histolytica-E. dispar complex was 80% sensitive and 99% specific. Differentiation of E. dispar from E. histolytica by the E. histolytica-specific test was 95% sensitive and 93% specific compared with zymodeme analysis. We conclude that the antigen detection test for the E. histolytica-E. dispar complex is more sensitive and specific than microscopy and that the E. histolytica-specific antigen detection test is as reliable and much more rapid than zymodeme analysis for the differentiation of E. histolytica from E. dispar.